Swedish economic integration into the European Union as a latecomer: Policy recommendations for Asian economic integration - Sang-Chul Pak (Asian Development Bank Institute (ADBI), 2020)
Sweden became a member of the European Union (EU) in 1995. Since then, she has been integrated into the EU's internal market under the Single Market Programme (SMP). Before Sweden's accession to the EU, she was a member of the European Free Trade Association (EFTA) signed with the EU in 1972. Later, Sweden signed to become a member of the European Economic Area (EEA) in 1992, which ensures participation in the SMP for nations that are not members of the EU. Despite her long membership, the twin faces of a Euro outsider still exist in public opinion. It is divided on the issue of further European integration. Her position has faced highly skeptical EU public opinion, particularly in the Economic and Monetary Union (EMU). Moreover, her positioning as a euro outsider has been perceived by the euro member nations as that of a selective supranationalist despite the desire of the Swedish government to build a good European nation with a mixed policy portfolio. The Swedish economy has benefited since its full accession to the EU compared with the EEA. This paper discusses whether the Swedish EU membership has contributed to the economic integration with the EU positively or not. Furthermore, it analyzes which actors have been the biggest winners and losers from the full accession to the EU. Last but not least it also investigates the challenges and prospects for the Swedish economy in the near future.
Keywords: F15; F16; 330; economic integration; single market; trade; FTA; EU; EMU